rhKGF-2 Attenuates Smoke Inhalation Lung Injury of Rats via Activating PI3K/Akt/Nrf2 and Repressing FoxO1-NLRP3 Inflammasome - Fu, Zhonghua; Jiang, Zhengying; Guo, Guanghua; Liao, Xincheng; Liu, Mingzhuo; Xiong, Zhenfang (Frontiers in Pharmacology, 2021)
Smoke inhalation injury is an acute pathological change caused by thermal stimulation or toxic substance absorption through respiratory epithelial cells. This study aims to probe the protective effect and mechanism of recombinant human keratinocyte growth factor 2 (rhKGF-2) against smoke inhalation-induced lung injury (SILI) in rats. The SILI was induced in rats using a smoke exposure model, which were then treated with rhKGF-2. The rat blood was collected for blood-gas analysis, and the levels of inflammatory factors and oxidative stress markers in the plasma were measured. The rat lung tissues were collected. The pathological changes and cell apoptosis were determined by hematoxylin-eosin (HE) staining and TdT-mediated dUTP nick end labeling (TUNEL) assay, and the PI3K/Akt/Nrf2/HO-1/NQO1, and FoxO1-NLRP3 inflammasome expression were verified by western blot (WB). Both of the human alveolar epithelial cell (HPAEpiC) and primary rat alveolar epithelial cell were exposed to lipopolysaccharide (LPS) for making in-vitro alveolar epithelial cell injury model. After treatment with rhKGF-2, GSK2126458 (PI3K inhibitor) and AS1842856 (FoxO1 inhibitor), the cell viability, apoptosis, inflammation, oxidative stress, reactive oxygen species (ROS), PI3K/Akt/Nrf2, HO-1/NQO1, and FoxO1-NLRP3 in HPAEpiC and primary rat alveolar epithelial cell were examined. The data suggested that rhKGF-2 reduced LPS-induced HPAEpiC cell and primary rat alveolar epithelial cell apoptosis and the expression of inflammatory factors and oxidative stress factors. Moreover, rhKGF-2 improved the blood gas and alleviated SILI-induced lung histopathological injury in vivo via repressing inflammation, NLRP3 inflammasome activation and oxidative stress. Mechanistically, rhKGF-2 activated PI3K/Akt pathway, enhanced Nrf2/HO-1/NQO1 expression, and attenuated FoxO1-NLRP3 inflammasome both in vitro and in vivo. However, pharmaceutical inhibition of PI3K/Akt pathway attenuated rhKGF-2-mediated protective effects against SILI, while suppressing FoxO1 promoted rhKGF-2-mediated protective effects. Taken together, this study demonstrated that rhKGF-2 mitigated SILI by regulating the PI3K/Akt/Nrf2 pathway and the FoxO1-NLRP3 axis, which provides new reference in treating SILI.